Heliconia Stricta Huber Behavior on Hybrid Constructed Wetlands Fed with Synthetic Domestic Wastewater - Villamar-Ayala, C (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Constructed wetlands (CWs) represent a highly ecient, eco-friendly and economic alternative for wastewater treatment in decentralized contexts. The adequate selection of the plants used in CWs plays a decisive role in the successful implementation and operation of this technology type. In this work, we studied the behavior of a native tropical plant (Heliconia stricta Huber) for the removal of organic matter and nutrients within a hybrid CW system fed with synthetic domestic wastewater. This hybrid system was composed of two wetlands, a vertical surface flow (VSF-CW) and a horizontal subsurface flow (HSSF-CW), connected in series and being operated with nominal hydraulic loading rates of 12 and 9 mm day-1, respectively. Results evidenced nitrification (nitrite concentration increased up to three times) but not denitrification because nitrate concentration increased in the final effluent. The average removal eciencies were 86.8%, 96.4%, and 57.0%, for COD, NH4+ and PO43-, respectively. On the other hand, the apical height, basal diameter, leaf length and width increased in relation to initial measurements (between 0.6-7.1%) in plants of both CWs, which demonstrated the ability of the plants to adapt to the operating conditions of the system. This promising performance observed when using Heliconia stricta Huber opens the need for further research and could be particularly interesting in CWs used in tropical areas. © 2020 by the authors.